(untitled) (Research, Society and Development, 2021)
Life expectancy has been increasing significantly worldwide, thereby increasing chronic diseases and geriatric syndromes, with urinary incontinence being one of them. Urinary incontinence is a complaint generally considered normal by the elderly and for this reason not reported in the consultations, it is in this scenario that the nurse who works in primary health care must question and welcome the elderly in nursing consultations. The objective of this work is to report the experience of nurses about the importance of carrying out the nursing consultation in elderly patients with Urinary Incontinence. The work is an experience report of the professional nurses, the nursing consultations took place in a basic health unit, located in a small city in the Central region of the State of Rio Grande do Sul, and involved elderly people with urinary complaints . The nursing consultation aims to assist the elderly with a welcoming listening based on scientificity, having as a principle the patient’s uniqueness offering an improvement in nursing care.